Immune parameter analysis of children with sickle cell disease on hydroxycarbamide or chronic transfusion therapy. (5th March 2015) - Nickel, Robert S.; Osunkwo, Ifeyinwa; Garrett, Aneesah; Robertson, Jennifer; Archer, David R.; Promislow, Daniel E.L.; Horan, John T.; Hendrickson, Jeanne E.; Kean, Leslie S.
Summary: Sickle cell disease (SCD) is increasingly appreciated as an inflammatory condition associated with alterations in immune phenotype and function. In this cross‐sectional study we performed a multiparameter analysis of 18 immune markers in 114 paediatric SCD patients divided by treatment group [those receiving hydroxycrabamide (HC, previously termed hydroxyurea), chronic transfusion (CT), or no disease‐modifying therapy] and 29 age‐matched African American healthy controls. We found global elevation of most immune cell counts in SCD patients receiving no disease‐modifying therapy at steady state. Despite the decrease in percentage of haemoglobin S associated with CT therapy, the abnormal cellular immune phenotype persisted in patients on CT. In contrast, in both univariate and multivariate analysis, treatment with HC was associated with normalization of the vast majority of leucocyte populations. This study provides additional support for HC treatment in SCD, as it appears that HC decreases the abnormally elevated immune cell counts in patients with SCD.